Effects of microwave irradiation on the decane-water interface in the presence of Triton X-100 - Hyde, A.; Horiguchi, M.; Minamishima, N.; Asakuma, Y.; Phan, Chi (Elsevier BV, 2017)
The present work investigates the influence of heating methods on the interfacial tension of the decane-water interface in the presence of the common industrial surfactant, Triton X-100. The work considers heating by conventional methods, such as a waterbath, in contrast to microwave irradiation. Use of the holm interface allowed the measurement of interfacial tension even during irradiation. The interfacial tension was found to increase as the samples were heated from 25 to 65 °C by the two methods. However, microwaves were found to elicit changes to the response of interfacial tension to changing temperature, resulting in a much more dramatic increase in interfacial tension. The impact of microwaves can be attributed to different networks of hydrogen bonding between surfactant and water at the interface and in the bulk.